Distinct expression patterns for type II topoisomerases IIA and IIB in the early foetal human telencephalon. Issue 3 (27th November 2015) - Harkin, Lauren F.; Gerrelli, Dianne; Gold Diaz, Diana C.; Santos, Chloe; Alzu'bi, Ayman; Austin, Caroline A.; Clowry, Gavin J.
Abstract: TOP2A and TOP2B are type II topoisomerase enzymes that have important but distinct roles in DNA replication and RNA transcription. Recently, TOP2B has been implicated in the transcription of long genes in particular that play crucial roles in neural development and are susceptible to mutations contributing to neurodevelopmental conditions such as autism and schizophrenia. This study maps their expression in the early foetal human telencephalon between 9 and 12 post‐conceptional weeks. TOP2A immunoreactivity was restricted to cell nuclei of the proliferative layers of the cortex and ganglionic eminences (GE), including the ventricular zone and subventricular zone (SVZ) closely matching expression of the proliferation marker KI67. Comparison with sections immunolabelled for NKX2.1, a medial GE (MGE) marker, and PAX6, a cortical progenitor cell and lateral GE (LGE) marker, revealed that TOP2A‐expressing cells were more abundant in MGE than the LGE. In the cortex, TOP2B is expressed in cell nuclei in both proliferative (SVZ) and post‐mitotic compartments (intermediate zone and cortical plate) as revealed by comparison with immunostaining for PAX6 and the post‐mitotic neuron marker TBR1. However, co‐expression with KI67 was rare. In the GE, TOP2B was also expressed by proliferative and post‐mitotic compartments. In situ hybridisation studies confirmed these patterns of expression, except that TOP2A mRNA is restricted to cells in the G2/M phase of division. Thus, during early development, TOP2A is likely to have a role in cell proliferation, whereas TOP2B is expressed in post‐mitotic cells and may be important in controlling expression of long genes even at this early stage.